2015
DOI: 10.1017/s0007114514003754
|View full text |Cite
|
Sign up to set email alerts
|

Chronic treatment with a tryptophan-rich protein hydrolysate improves emotional processing, mental energy levels and reaction time in middle-aged women

Abstract: Common pharmacological treatments of mood disorders aim to modulate serotonergic neurotransmission and enhance serotonin levels in the brain. Brain serotonin levels are dependent on the availability of its food-derived precursor essential amino acid tryptophan (Trp). We tested the hypothesis that delivery of Trp via food may serve as an alternative treatment, and examined the effects of a Trp-rich, bioavailable dietary supplement from egg protein hydrolysate on cognitive and emotional functions, mood state, an… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
40
0
1

Year Published

2016
2016
2024
2024

Publication Types

Select...
6
2

Relationship

1
7

Authors

Journals

citations
Cited by 57 publications
(42 citation statements)
references
References 46 publications
1
40
0
1
Order By: Relevance
“…Tryptophan-containing foods improved sleep indices compared with controls [15,27]. For example, compared with controls, an increase in total sleep time, sleep efficiency, and immobile time was noted after a week of tryptophan-rich (60 mg) cereal consumption in older adults [15].…”
Section: Tryptophan Consumption and Depletionmentioning
confidence: 92%
See 1 more Smart Citation
“…Tryptophan-containing foods improved sleep indices compared with controls [15,27]. For example, compared with controls, an increase in total sleep time, sleep efficiency, and immobile time was noted after a week of tryptophan-rich (60 mg) cereal consumption in older adults [15].…”
Section: Tryptophan Consumption and Depletionmentioning
confidence: 92%
“…Five studies were classified under this category based on the investigation of the effects of either tryptophan consumption [15,27] or acute tryptophan depletion [17,28,29] on sleep in otherwise healthy adults. All of the studies examining tryptophan depletion used PSG to measure sleep, while the studies investigating tryptophan consumption utilized actigraphy [15] and sleep diaries [27]. Table 1 summarizes the characteristics and outcomes of these studies.…”
Section: Tryptophan Consumption and Depletionmentioning
confidence: 99%
“…Brain 5-HT synthesis rates are reportedly 50 % lower in women than men (105) , and ATD causes greater lowering of mood in women than men (106) . In some studies, women also appear to be more sensitive to, or to benefit more from, TRP supplementation; indeed, some researchers chose to study women only for these reasons (97,98) . Furthermore, sex interacts with serotonergic gene polymorphisms in several systems, including 5-HTTLPR, TPH1, TPH2 and MAO-A (67,107) , and these interactions can be further moderated by stress (108)(109)(110)(111) .…”
Section: Role Of Genetics In Moderating Effects Of L-tryptophan Supplmentioning
confidence: 99%
“…Mori et al reported that soybean b-conglycinin hydrolysate with thermolysin had antidepressant activity via the vagus nerve in mice (18). Several groups reported that egg protein hydrolysate promoted mood and emotional function in humans (19)(20)(21). These results suggest that regulation of incentive may be impacted by food-derived peptides.…”
Section: Discussionmentioning
confidence: 99%